(untitled) (KMC Journal, 2025)
The early childhood development stage is highly critical in setting up cognitive and overall well-being. The purposes of the study were to explore how family disputes affect the learning and development of children and to assess the challenges and coping strategies of mothers at a time of family dispute. The study used phenomenological approach of qualitative research design among the mother of early childhood development (ECD) children in Rupandehi district of Nepal. Semi-structured interviews were taken. Thirteen mothers were selected using purposive sampling method from ECD centers and home creating comfortable environment. After permission, all interviews were audio-recorded and transcribed. The data were analyzed using thematic analysis approach. The findings showed that the physical presence of father, a destructive home environment, children’s imitation of family disputes, and parental alcohol consumption have negatively impacted child learning while maternal coping strategies in family disputes have had a positive effect on child learning and development. Family conflict, emotional distress of children, destructive home environment, fight between couple have negative effect on children’s learning whereas positive family dynamics support their effective learning. Many mothers have been facing the challenge of domestic violence. The study concluded that the mothers possess a range of coping skills to manage family disputes. If both parents make a conscious effort to avoid conflict in front of their children, its negative influence can be significantly reduced as it directly or indirectly affects children’s learning and development. Hence, a conscious and active cooperation with emotional regulation by both mother and father is essential for stable child development.